EDUKASI PROGRAM PROLANIS TERHADAP ASUPAN NATRIUM, KALIUM DAN SERAT SERTA TEKANAN DARAH PADA PASIEN HIPERTENSI DI WILAYAH KERJA PUSKESMAS KUTA ALAM BANDA ACEH - Mulyani, Nunung Sri; Kurniati, Fitrah; Ardiansyah, Ardiansyah (Jurnal Nutrire Diaita (Ilmu Gizi), 2021)
Hypertension is one of the important factors as a trigger for non-communicable diseases such as heart disease, stroke, so it is necessary to monitor the health of hypertensive patients, one of which is the Chronic Disease Management Program (PROLANIS). Research Objectives: to determine the relationship of Prolanis Program to sodium, potassium and fiber intake and blood pressure in hypertensive patients in the working area of Kuta Alam Health Center, Banda Aceh City.  This type of research is analytic descriptive using a cross sectional approach. The study was conducted in February 2019 in the work area of the Kuta Alam Banda Aceh puskesmas. Sampling was done with a total sampling of 35 hypertensive patients. Data collected included sodium intake, potassium and fiber intake using the food recall form and blood pressure data using sphygmomanometer measurements. Data analysis using chi-square statistical tests using univariate and bivariate analysis.  There is a relationship between prolanis education on sodium intake in hypertensive patients with P Value = 0.004, There is a relationship between prolanis education on potassium intake in hypertensive patients with P Value = 0.044. There is a relationship between prolanis education on fiber intake in hypertensive patients with P Value = 0.002 and there is a relationship between prolanis education on blood pressure in hypertensive patients with P Value = 0.001. Prolanis education programs affect the intake of sodium, potassium, fiber and blood pressure in hypertensive patients. Keywords: Education, Sodium intake, Potassium, Fiber, Blood pressure.